2021
DOI: 10.1055/a-1375-8151
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic internal drainage and low negative-pressure endoscopic vacuum therapy for anastomotic leaks after oncologic upper gastrointestinal surgery

Abstract: Background: Endoscopic internal drainage (EID) with double pigtail stents and low negative pressure endoscopic vacuum therapy (EVT) are treatment options for leakages after upper GI oncologic surgery. We aimed to compare the effectiveness of these techniques. Patients and methods: Between 2016 and 2019, patients treated with EID in five centers in France and with EVT in Göttingen, Germany were included and retrospectively analyzed using univariate analysis. Pigtails were changed every 4 weeks, EVT was repeat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
16
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 12 publications
0
16
1
Order By: Relevance
“…18,19 Compared to endoluminal vacuum therapy, patients with EID can generally commence oral feeding earlier, EID procedures can be performed without a general anesthetic, and there is less need for frequent and repeated endoscopic procedures. [21][22][23] Nine out of 12 patients (75%) were successfully managed with EID using DPT in this case series. DPT allows for early oral nutritional feeding and potentially avoids conventional external drainage.…”
Section: Discussionmentioning
confidence: 75%
“…18,19 Compared to endoluminal vacuum therapy, patients with EID can generally commence oral feeding earlier, EID procedures can be performed without a general anesthetic, and there is less need for frequent and repeated endoscopic procedures. [21][22][23] Nine out of 12 patients (75%) were successfully managed with EID using DPT in this case series. DPT allows for early oral nutritional feeding and potentially avoids conventional external drainage.…”
Section: Discussionmentioning
confidence: 75%
“…Morykwas et al showed in a porcine model that an effective increase of wound blood flow was reached at a negative pressure of − 125 mmHg, which lead to optimal oxygenation, neoangiogenisis and elaboration of growth factors and consequently to a faster tissue granulation [33]. Contrary to this, Jung et al presented a clinical trial in which they achieved a sealing rate of 78.3% in an AL subgroup analysis for the mono-therapy of EVT with a pressure between − 20 and − 50 mmHg [34]. We have used − 125 mmHg since we introduced this treatment option in our clinic [14].…”
Section: Discussionmentioning
confidence: 99%
“…A study by Jung et al Comparing EID vs. EVT in defects after oncologic surgery confirmed high healing success after EID with 100% vs. 85.2% after EVT [ 99 ].…”
Section: Endoscopic Techniquesmentioning
confidence: 99%